Traveling interface modulations and anisotropic front propagation in ammonia oxidation over Rh(110) - Rafti, Matías (2015)
The bistable NH3 + O2 reaction over a Rh(110) surface was explored in the pressure range 10−6–10−3 mbar and in the temperature range 300–900 K using photoemission electron microscopy and low energy electron microscopy as spatially resolving methods. We observed a history dependent anisotropy in front propagation, traveling interface modulations, transitions with secondary reaction fronts, and stationary island structures.